Statistical Meso-Mechanics of Damage and Failure: How Microdamage Induces Disaster Series Publication of Multiscale Mechanics - Bai, Yilong; Xia, Mengfen; Ke, Fujiu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book introduces a trans-scale framework necessary for the physical understanding of breakdown behaviors and presents some new paradigm to clarify the mechanisms underlying the trans-scale processes. The publication of this book based on the interaction of mechanics and statistical physics can help to deepen the understanding of how microdamage induces disaster and benefit the forecasting of the occurrence of catastrophic rupture. The readers of the book would be graduate students, researchers, engineers working on civil, mechanical and geo-engineering, etc. However, people with various background but interested in disaster reduction and forecasting, like applied physics, geophysics, seismology, etc., may also be interested in the book. .
Introduction:Damage and failure of heterogeneous media: basic features and common characteristics.-Framework of statistical meso-mechanics: why and how statistical meso-mechanics is -- Mathematical essentials in statistical meso-mechanics -- Part A Quasi-statically Statistical Evolution of Deformation and Damage in Media with Mesoscopic Heterogeneities:Coupled average (CA) -- Elastic and statistically-brittle (ESB) constitutive model,Global mean field (GMF) approximation -- Continuous bifurcation and localization of deformation,Regional mean field (RMF) approximation -- Size effect -- Experimental issues related to statistical meso-mechanics -- Numerical issues related to heterogeneous meso-elements -- Application to failure wave (one-dimensional strain state) -- Application to metal foams -- Application to concrete under bi-axial compression -- Part B Time-Dependent Processes of Micro-damage Population: Background andmethodology -- Fundamental equation of microdamage evolution -- General solution to evolution of microdamage number density -- Closed formulation of continuum damage based on microdamage evolution -- Deborah number and its significance in the evolution of microdamage -- Spallation - tensile failure resulting from microcracks under stress waves -- Short fatigue cracks -- More cases of time-dependent processes related to microdamage -- Brief summary of Part B -- Part C Critical Catastrophe: Evolution induced catastrophe (EIC) -- Energy transfer and catastrophe considering damage localization -- Sample specificity and Trans-scale Sensitivity -- Critical Sensitivity and power-law singularity of catastrophe -- Great earthquake: the catastrophic rupture in Earth's Crust -- Perspective. .
Keywords: Materials -- Analysis; Geotechnical engineering; Mechanics, Applied; Solids; Natural disasters; Mechanics; Nonlinear Optics; Characterization and Analytical Technique; Geotechnical Engineering and Applied Earth Sciences; Solid Mechanics; Natural Hazards; Classical Mechanics; Nonlinear Optics